Lithologic and morphometric characteristics of the Chure River Basin, Central Nepal - Tamrakar, Naresh Kazi; Khakurel, Dharmendra (Bulletin of the Department of Geology, 2013)
The Chure River Basin (CRB) is a small basin (width 5.75 km, length 9.74 km, perimeter 32.35 km and area 35.23 km2) with three sub-watersheds, and is crossed by the Tribhuvan Highway that may be threatened by riverine and allied processes. The geology and morphometry of the basin were studied to search for status of the basin development andriver dynamism. The Chure River is a sixth order river fed by rainstorm, and has length ratio of 2.79, indicating nearly three times the average length of its fifth order segment, showing notable competency. The mean bifurcation ratio of the Chure River is 3.20, showing immature nature of the CRB. Drainage texture (DT) varies from moderate (0.64–0.96) to very fine (0–0.32). The Chure River is sinuous (K =1.18). The relative relief (RR) is moderately low (15–30) to moderately high (120–240) and dissection index (DI) is moderate (0.2–0.3) to high (0.3–0.4). The CRB carries varied lithology; gravelly to coarse sandy and medium sandy and muddy, from the north to the south extension of the basin. Fine to very fine DT found in large areas because of loosely consolidated and soft lithology. Even where rocks are stiff, the presence of discontinuity has perhaps influenced the DT. Very fine to fine DT coupled with elongate nature of the basin (as indicated by low value of form factor, 0.37) is vulnerable to greater competency of the river during high rainfall. RR slope and DI are found to be high in the cliff- forming lithology (stiff and well cemented), and low in other areas. High dissection, high slopes and high relief show active and immature nature of the CRB, indicating susceptibility of further incision of the Siwalik Hills and aggravation of erosion and slope movements by the immature rivers in the CRB. Presence of knick points along the river profile reflects affinity of the river to incision. The sinuosity, radius of curvature, and bifurcation ratio, all indicate immaturity of the basin. The hypsometric analysis indicates inverse relationship between the elevation and the cumulative %area, showing active erosional condition of the basin. DOI: http://dx.doi.org/10.3126/bdg.v15i0.7416 Bulletin of the Department of Geology, Vol. 15, 2012, pp. 35-48